Beam characteristics of the first clinical 360° rotational single gantry room scanning pencil beam proton treatment system and comparisons against a multi‐room system. Issue 9 (13th August 2020) - Shang, Charles; Evans, Grant; Rahman, Mushfiqur; Lin, Liyong
Abstract: Purpose: The purpose of this study was to present the proton beam characteristics of the first clinical single‐room ProBeam Compact™ proton therapy system (SRPT) and comparison against multi‐room ProBeam™ system (MRPT). Materials and Methods: A newly designed SRPT with proton beam energies ranging from 70 to 220 MeV was commissioned in late 2019. Integrated depth doses (IDDs) were scanned using 81.6 mm diameter Bragg peak chambers and normalized by outputs at 15 mm WET and 1.1 RBE offset, following the methodology of TRS 398. The in‐air beam spot profiles were acquired by a planar scintillation device, respectively, at ISO, upper and down streams, fitted with single Gaussian distribution for beam modeling in Eclipse v15.6. The field size effect was adjusted for the best overall accuracy of clinically relevant field QAs. The halo effects at near surface were quantified by a pinpoint ionization chamber. Its major dosimetric characteristics were compared against MRPT comparable beam dataset. Results: Contrast to MRPT, an increased proton straggling in the Bragg peak region was found with widened beam distal falloffs and elevated proximal transmission dose values. Integrated depth doses showed 0.105–0.221 MeV (energy sigma) or 0.30–0.94 mm broader Bragg peak widths (Rb80 –Ra80 ) for 130 MeV or higher energy beams and up to 0.48–0.79 mm extended distal falloffs (Rb20 –Rb80 ). Minor differences were identified in beam spot sizes, spot divergences, proton particles/MU, and field size output effects. High passing scores are reported for independent end‐to‐end dosimetry checks by IROC and for initial 108 field‐specific QAs at 3%/3 mm Gamma index with fields regardless with or without range shifters. Conclusions: The author highlighted the dosimetry differences in IDDs mainly caused by the shortened beam transport system of SRPT, for which new acceptance criteria were adapted. This report offers a unique reference for future commissioning, beam modeling, planning, and analysis of QA and clinical studies.